ACCOUNTING DOCTORAL PROGRAMS IN AACSB COLLEGES OF BUSINESS ADMINISTRATION. - Stone, Williard E. (The Accounting Review, 1965)
Abstract A survey of doctoral programs with accounting majors or concentrations has been completed with the cooperation of all colleges of business administration which are members of the American Association of Collegiate Schools of Business (AACSB). Originally intended as a part of the work of the American Accounting Associations 1964 Committee on Courses and Curriculum-Doctoral Programs, the results of the survey were not included in their report because the members of the committee favored a dynamic approach dealing with the direction doctoral programs should take in the future. The survey, largely concerned with the present status of doctoral programs, may be labeled by some as a "nose counting" effort. Many of the participating colleges, however, expressed a desire to learn the results of the survey and this article will attempt to summarize the information so kindly supplied by representatives of all 113 colleges. Of the 113 AACSB colleges, 34 percent offer a doctoral program with a major or concentration in accounting as of the 1963-64 scholastic year.